2022
DOI: 10.3390/min12080946
|View full text |Cite
|
Sign up to set email alerts
|

Paleoenvironmental and Bio-Sequence Stratigraphic Analysis of the Cretaceous Pelagic Carbonates of Eastern Tethys, Sulaiman Range, Pakistan

Abstract: The Cretaceous pelagic carbonate succession, i.e., Goru Formation was studied in the Chutair Section, Sulaiman Range, representing part of the eastern Tethys for the paleoenvironment and bio-sequence stratigraphy. Eight planktonic foraminiferal biozones are identified which include: 1. Muricohedbergella planispira Interval Zone; 2. Ticinella primula Interval Zone; 3. Biticinella breggiensis Interval Zone; 4. Rotalipora appenninica Interval Zone; 5. Rotalipora cushmani Total Range Zone; 6. Whiteinella archeocre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…Similar resources have also been reported from the Ordovician carbonates of the Ordos and Tarim basins of China (Wei et al, 2017;Chen et al, 2020). Recent studies have also focused on such potential tight carbonates from various parts of the world including offshore Malaysia (Bashir et al, 2021), Pakistan (Ali et al, 2022;Ullah et al, 2022), and China (Jiang et al, 2022). Three recent works by Boutaleb et al (2021), Radwan et al (2021) and Fea et al (2022) reported selfsourcing and self-storing unconventional carbonate intervals from the African continent.…”
Section: Introductionmentioning
confidence: 99%
“…Similar resources have also been reported from the Ordovician carbonates of the Ordos and Tarim basins of China (Wei et al, 2017;Chen et al, 2020). Recent studies have also focused on such potential tight carbonates from various parts of the world including offshore Malaysia (Bashir et al, 2021), Pakistan (Ali et al, 2022;Ullah et al, 2022), and China (Jiang et al, 2022). Three recent works by Boutaleb et al (2021), Radwan et al (2021) and Fea et al (2022) reported selfsourcing and self-storing unconventional carbonate intervals from the African continent.…”
Section: Introductionmentioning
confidence: 99%
“…The eighth paper, by Ullah et al [8], focuses on studying the Goru Formation in the Chutair Section, Sulaiman Range, Pakistan, representing part of the eastern Tethys. The paleoenvironment and bio-sequence stratigraphy were studied in the Cretaceous pelagic carbonate succession.…”
mentioning
confidence: 99%